Effects of Organizational Learning Culture and Developmental Feedback on Engineers’ Career Satisfaction in the Manufacturing Organizations in Malaysia - Desa, Nasina Mat; Asaari, Muhammad Hasmi Abu Hassan (Universiti Sains Malaysia, 2016)
The purpose of this paper is to test the hypotheses that relations between organizational learning culture, developmental feedback and career satisfaction in the manufacturing organizations. A sample of 155 engineers was drawn from two major manufacturing organizations located in the Northern Malaysia. Participation in the research was voluntary and data were gathered by means of a survey questionnaire. Multiple regression results provided support for the direct impact of organizational learning culture and developmental feedback on the engineer’s career satisfaction. Key implications of the survey findings both of the theory and practice are discussed, potential limitations are specified, and directions for future research are suggested